2013
DOI: 10.1007/s12094-013-1106-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of miR-9 expression as a poor prognostic biomarker in patients with non-small cell lung cancer

Abstract: MiR-9 was up-regulated in non-small cell lung cancer tissues and correlated with adverse clinical features and unfavorable survival, indicating that miR-9 might be involved in non-small lung cancer progression and could serve as a promising biomarker for further risk stratification in the treatment of this cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 30 publications
4
57
0
3
Order By: Relevance
“…Second, the study was conducted based on the available patient samples from both lung squamous cell carcinoma and lung adenocarcinoma and elucidated critical regulatory mechanisms for NSCLC. While we pointed this out as a limitation, several studies regarded these two subtypes together in order to infer critical biomolecules that have potential implications for the pathology of NSCLC (Raponi et al 2006;Ma et al 2011;Xu et al 2014). For example, after analyzing 116 tumor samples (69 squamous cell carcinoma and 47 adenocarcinoma) and adjacent normal lung tissue samples, Xu et al (2014) demonstrated that high miR-9-5p expression is associated with poorer progression-free survival (P-value < 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the study was conducted based on the available patient samples from both lung squamous cell carcinoma and lung adenocarcinoma and elucidated critical regulatory mechanisms for NSCLC. While we pointed this out as a limitation, several studies regarded these two subtypes together in order to infer critical biomolecules that have potential implications for the pathology of NSCLC (Raponi et al 2006;Ma et al 2011;Xu et al 2014). For example, after analyzing 116 tumor samples (69 squamous cell carcinoma and 47 adenocarcinoma) and adjacent normal lung tissue samples, Xu et al (2014) demonstrated that high miR-9-5p expression is associated with poorer progression-free survival (P-value < 10…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TGFBR2 was reported as a direct target of miR-17-5p (Dews et al 2010). So far, the expression pattern for miR-9-5p in lung tumor versus non-tumor samples has been inconsistently reported: up-regulation (Crawford et al 2009;Kang et al 2013;Xu et al 2014), downregulation (Yanaihara et al 2006), or insignificant change in expression (Jusufovic et al 2012). To the best of our knowledge, there is no report on miR-130b-3p expression in NSCLC.…”
Section: Systematic Filtering Of Critical Mirnas In Nsclcmentioning
confidence: 97%
“…[8][9][10] MiRNAs are present in a stable form in human serum and plasma, suggesting the potential use of circulating miRNAs as stable blood-based markers for the detection of cancer or other human diseases. [11][12][13] MicroRNA-9 is upregulated in many tumour types including colorectal, 14 breast 15 and non-small cell lung cancer, 16 but its role in the progression of osteosarcoma remains unknown. The aim of this study, therefore, was to analyse the association between serum miR-9 concentrations and clinicopathological features and prognosis, in patients with osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies performed in cancer ce ll lines or animal models of various cancers suggest that, miRNAs can function as tumor suppressors, oncogenes, and regulate cancer pathways (Farazi et al, 2011). Aberrant expression of specific miRNAs has been reported in many tumor types 1 such as CRC, breast cancer, cervical cancer, non-small cell lung cancer, ovarian cancer and bladder cancer as well as being associated with patients' survival data, metastasis, and other clinicopathological factors (Toyama et al, 2012;Wan et al, 2012;Shen et al, 2013;Wang et al, 2013;Xiao et al, 2013;Liu et al, 2014;Xu et al, 2014). A previous study showed that miR-32 expression was upregulated in CRC tissues, and high expression was significantly correlated with the tumor stage, distal metastases and poor prognoses (Wu et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%